2006
DOI: 10.1542/peds.2006-0841
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status in Children and Young Adults With Inflammatory Bowel Disease

Abstract: OBJECTIVES-Previous studies of vitamin D status in pediatric patients with inflammatory bowel disease have revealed conflicting results. We sought to report (1) the prevalence of vitamin D deficiency (serum 25-hydroxy-vitamin D concentration ≤15 ng/mL) in a large population with inflammatory bowel disease, (2) factors predisposing to this problem, and (3) its relationship to bone health and serum parathyroid hormone concentration.PATIENTS AND METHODS-A total of 130 patients (8-22 years of age) with inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
144
4
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(172 citation statements)
references
References 55 publications
18
144
4
6
Order By: Relevance
“…The biological activity of 1,25(OH) 2 D 3 is mediated by the vitamin D receptor (VDR), a member of the nuclear hormone receptor superfamily (19). A growing body of epidemiological data has documented an association between vitamin D deficiency and increased risk of IBD (20)(21)(22), including both CD and UC (23)(24)(25)(26)(27)(28)(29)(30). A high prevalence of vitamin D deficiency was reported in patients with established as well as newly diagnosed IBD (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…The biological activity of 1,25(OH) 2 D 3 is mediated by the vitamin D receptor (VDR), a member of the nuclear hormone receptor superfamily (19). A growing body of epidemiological data has documented an association between vitamin D deficiency and increased risk of IBD (20)(21)(22), including both CD and UC (23)(24)(25)(26)(27)(28)(29)(30). A high prevalence of vitamin D deficiency was reported in patients with established as well as newly diagnosed IBD (31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%
“…The deficiency appeared mostly in winter and autumn and was not connected with the location and the severity of the disease [22]. Whereas in the studies conducted in Boston among children with IBD, the deficit of vitamin D3 was found in 34.6% with the similar frequency in the group with CD and UC (ulcerative colitis), more frequently among black patients, in winter, with the affected upper part of alimentary tract, and among those who were not supplemented with vitamin D3, with more severe course of disease -low BMI, low concentration of albumins, high ESr, and at the beginning of the disease [23]. Ethnic factors may also play a part in the status of vitamin D3 among patients with IBD -more frequent deficits were found among black children as well as among adults of the southern-Asian origin compared to the Caucasians [23,24].…”
Section: The Contribution Of Vitamin D In the Inflammatory Bowel Disementioning
confidence: 80%
“…This lack of correlation has been reported in the literature by several authors [18,19] who, among other mechanisms, also suggest a possible important role of vitamin D at the intestinal level that would allow a greater absorption of vitamin D secondary to the beneficial effects of a longer therapy and therefore a better control of the activity of the disease itself. In contrast, other authors have found an inverse correlation between the duration of disease and serum levels of vitamin D, especially in patients with Crohn's disease [20].…”
Section: International Journal Of Digestive Diseasesmentioning
confidence: 82%